Inisiasi Hubungan Seksual Pada Mahasiswa Di Kota Bandar Lampung - Roro Rukmi W P (JUKE Unila, 2012)
Adolescent sexual behavior tends to be permissive. There is a group of university students in Bandar Lampung who like clubbing. According to the researcher's assumption they have permissive attitude to premarital sexual intercourse. According to Symbolic Interactionism Theory, sexual behavior is based on sexual scripting. The study is aimed to understand sexual scripting focusing on sexual initiation  among university students who like clubbing. This is a qualitative study using in depth-interview of 11 respondents, using purposive sampling technique. The data is analyzed by thematic content analysis.  The results show respondents are 18-24 years old. Most of sexual initiation occurs in 1 – 4 months after first dating. Men usually start indirectly by asking their partner go to certain places which they feel comfort and free for sexual activities: their own or friends' rent rooms, beach which rent some rooms, or hotel. The places are symbolized as intimate places or if partner ask them to those places it means that they will have sex relationship. Few of them asked their partner directly